Crosstalk Between SUMO and Ubiquitin-Like Proteins: Implication for Antiviral Defense - Chelbi-Alix, Mounira K.; Thibault, Pierre (Frontiers in Cell and Developmental Biology, 2021)
Interferon (IFN) is a crucial first line of defense against viral infection. This cytokine induces the expression of several IFN-Stimulated Genes (ISGs), some of which act as restriction factors. Upon IFN stimulation, cells also express ISG15 and SUMO, two key ubiquitin-like (Ubl) modifiers that play important roles in the antiviral response. IFN itself increases the global cellular SUMOylation in a PML-dependent manner. Mass spectrometry-based proteomics enables the large-scale identification of Ubl protein conjugates to determine the sites of modification and the quantitative changes in protein abundance. Importantly, a key difference amongst SUMO paralogs is the ability of SUMO2/3 to form poly-SUMO chains that recruit SUMO ubiquitin ligases such RING finger protein RNF4 and RNF111, thus resulting in the proteasomal degradation of conjugated substrates. Crosstalk between poly-SUMOylation and ISG15 has been reported recently, where increased poly-SUMOylation in response to IFN enhances IFN-induced ISGylation, stabilizes several ISG products in a TRIM25-dependent fashion, and results in enhanced IFN-induced antiviral activities. This contribution will highlight the relevance of the global SUMO proteome and the crosstalk between SUMO, ubiquitin and ISG15 in controlling both the stability and function of specific restriction factors that mediate IFN antiviral defense.